The Implementation of Sustainable Supply Chain in The Beauty and Personal Care Industry in Indonesia: The Natural Resource-Based View - Salsabila, Natasha Vidi; Berliana, Sheilla Ananda; Yunus, Erlinda Nusron (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2025)
This study aims to understand the knowledge of the beauty and personal care industry in Indonesia about sustainable supply chain and assess the impact of consumer views about sustainable supply chain implementation on corporate image and purchase intention. Specifically, the study tests the relationships between customers’ knowledge regarding firms’ sustainable supply chain practices and firms’ corporate image. Sustainable supply chain practices are measured through the extent of sustainable procurement, sustainable warehousing, sustainable product design, sustainable energy, sustainable transportation, reverse logistics, and sustainable waste management. Customers’ perception on the corporate image would further increase their purchase intention. The research uses a quantitative approach by surveying 438 beauty and personal care product users. The results show that sustainable waste management is the most recognized and perceived implementation that contributes to a good corporate image regarding sustainability. Therefore, beauty and personal care companies can leverage the customer perception of sustainable supply chains by emphasizing sustainable waste management through different strategies and educating customers on sustainable supply chain practices. The findings of this study provide valuable insight into the practical effectiveness of sustainable chain supply in the beauty and personal care industry and provide input to future sustainability efforts on the environment, society, and economics.